The Needs and Experiences of Patients on Pain Education and the Clinical Reasoning of Physical Therapists Regarding Cancer-Related Pain. A Qualitative Study - Eisen, Tessa; Kooijstra, Eline Menje; Groeneweg, Ruud; Verseveld, Michelle; Hidding, Janine (Frontiers in Pain Research, 2021)
Objective: This study offers direction for interaction between physical therapists and patients about cancer-related pain during physical training. The study may increase awareness of rehabilitation strategies for cancer-related pain during and after cancer treatment. Methods: Qualitative study, evaluating results of two qualitative studies. Data has been collected using semi-structured interviews, in which topics were discussed with patients and physical therapists. Respondents were adult patients with cancer in the Northern Netherlands with moderate to severe pain who followed physical training with a (oncologic) physical therapist. The physical therapists were respondents specialized in oncology and working with patients with cancer in a primary care setting in in the Netherlands. Data were analyzed using thematic analysis. Results: Eighteen patients and fifteen physical therapists were interviewed. Data was categorized in statements regarding “patients' needs”, “patients' experiences” and “clinical reasoning of the physical therapist”. “Patients' needs” for education were personal and included needs for information about the cause, course and effect of pain in relation to cancer and/or medical treatment, needs for practical tools for reducing pain, needs for strategies dealing with pain in daily activities, and needs for information about additional treatment and care options. When discussing ‘patients’ experiences', patients mentioned that physical therapists are cautious to express their expectations of the progress of pain and to offer pain education with respect to the cause of pain, dealing with pain and limitations in daily life, exercising, posture, learning self-care and information about additional treatment and care options in cancer-related pain. Patients provided insight into their educational, mental, and social support relative to experiences with physical therapists. Additionally, when discussing the communication they experienced with physical therapists, patients used descriptors such as accessibility, empathy, trust, knowledge and eliminating uncertainties. Interviews with physical therapists regarding their clinical reasoning process in cancer-related pain described that they identified pain from anamnesis (medical history review) and performed screening and analysis for pain secondary to cancer (treatment), as type of pain and pain influencing factors. Thoughts and experiences about pain, the use of pain clinometry, the establishment of objectives and interventions for physical therapy and multidisciplinary treatment of cancer-related pain were also described. Conclusion: Patients with cancer-related pain during physical training have personal needs regarding pain education and experience that specialized oncologic physical therapists focus on patient-centered information and self-management support. Specialized oncologic physical therapists analyze pain in the anamnesis and keep in mind the origin and impact of pain for the patient during screening and treatment. Different methods of pain management are used. It is recommended that physical therapists who give physical training take the initiative to repeatedly discuss pain.